Standard Taxation Gaps & Reforms: A Critical Review of Revenue Policies of Kurdistan Region of Iraq - Pankaj Dixit; Rahim Jafar Mohammad Sharif (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
This study is about the Iraq but the core area is focused on its independent province Kurdistan. The Kurdistan is an autonomous province of federal republic of Iraq having separate legislative assembly namely; parliament. Still it is under developed region and financially depend on Iraqi federal budget. Tax policies of the federal Iraq and its region Kurdistan are not well- structured as per international standard. These policies have a huge gap in purview of sound revenue practices. Standard taxation gaps are the gaps between universal tax practices and the traditional existing tax practices, which are affecting the tax revenue and also affecting the sound practices of tax administration. The primary purpose of this article is to find out the gaps in taxation system and its existing administration policies and critically examines the facts of Kurdistan tax policies in the light of universal standard sound practices within the scope of Iraqi constitution and also find out, how can Kurdistan get more revenue by revising its existing tax policies and what are the  necessities for filling these existing gaps.